Signal termination in bacterial chemotaxis: CheZ mediates dephosphorylation of free rather than switch-bound CheY. - Bren, A (1996)
Chemotaxis in bacteria is controlled by regulating the direction of flagellar rotation. The regulation is carried out by the chemotaxis protein CheY. When phosphorylated, CheY binds to FliM, which is one of the proteins that constitute the "gear box" (or "switch") of the flagellar motor. Consequently, the motor shifts from the default direction of rotation, counterclockwise, to clockwise rotation. This biased rotation is terminated when CheY is dephosphorylated either spontaneously or, faster, by a specific phosphatase, CheZ. Logically, one might expect CheZ to act directly on FliM-bound CheY. However, here we provide direct biochemical evidence that, in contrast to this expectation, phosphorylated CheY (CheY approximately P), bound to FliM, is protected from dephosphorylation by CheZ. The complex between CheY approximately P and FliM was trapped by cross-linking with dimethylsuberimidate, and its susceptibility to CheZ was measured. CheY approximately P complexed with FliM, unlike free CheY approximately P, was not dephosphorylated by CheZ. However, it did undergo spontaneous dephosphorylation. Nonspecific cross-linked CheY dimers, measured as a control, were dephosphorylated by CheZ. No significant binding between CheZ and any of the switch proteins was detected. It is concluded that, in the termination mechanism of signal transduction in bacterial chemotaxis, CheZ acts only on free CheY approximately P. We suggest that CheZ affects switch-bound CheY approximately P by shifting the equilibrium between bound and free CheY approximately P.